2018
DOI: 10.3748/wjg.v24.i14.1550
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance for healed erosive esophagitis: Phase III comparison of vonoprazan with lansoprazole

Abstract: AIMTo compare vonoprazan 10 and 20 mg vs lansoprazole 15 mg as maintenance therapy in healed erosive esophagitis (EE).METHODSA total of 607 patients aged ≥ 20 years, with endoscopically-confirmed healed EE following 8 wk of treatment with vonoprazan 20 mg once daily, were randomized 1:1:1 to receive lansoprazole 15 mg (n = 201), vonoprazan 10 mg (n = 202), or vonoprazan 20 mg (n = 204), once daily. The primary endpoint of the study was the rate of endoscopically-confirmed EE recurrence during a 24-wk maintenan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
90
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(101 citation statements)
references
References 26 publications
4
90
0
7
Order By: Relevance
“…Erosive esophagitis recurrence rate at 24 weeks was 5.1%. The safety profiles of VPZ 10 and 20 mg were similar to that of LPZ 15 mg in patients with healed erosive esophagitis [45]. The results of this study showed that over a period of 12 months on demand 10 mg VPZ maintained endoscopic remission (86.0%) in patients who had been successfully treated by VPZ 20 mg for RE refractory to PPIs.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Erosive esophagitis recurrence rate at 24 weeks was 5.1%. The safety profiles of VPZ 10 and 20 mg were similar to that of LPZ 15 mg in patients with healed erosive esophagitis [45]. The results of this study showed that over a period of 12 months on demand 10 mg VPZ maintained endoscopic remission (86.0%) in patients who had been successfully treated by VPZ 20 mg for RE refractory to PPIs.…”
Section: Discussionsupporting
confidence: 54%
“…Since the mean percent time of gastric pH 4 or higher by standarddose PPI was approximately 50-65% [29,[42][43][44], the efficacy of VPZ 10 mg could be similar to or higher than that of standard-dose PPI. Ashida et al [45] confirmed the noninferiority of VPZ 10 and 20 mg to LPZ 15 mg as the 24-week maintenance therapy for patients with healed erosive esophagitis. Erosive esophagitis recurrence rate at 24 weeks was 5.1%.…”
Section: Discussionmentioning
confidence: 93%
“…Various clinical studies have reported that vonoprazan is comparable or superior to PPIs for the treatment of GERD including EE and NERD. [ 19 , 20 ] However, it remains unclear whether vonoprazan is superior to PPIs for the treatment of GERD. Therefore, a meta-analysis and systematic review in this field may lead a more accurate conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…Continuous administration of vonoprazan (10 mg/day or 20 mg/day) is more efficacious than that of lansoprazole (15 mg/day) in maintaining healed erosive esophagitis. 44 Therefore, at present, the optimal maintenance strategy for erosive esophagitis is continuous administration of vonoprazan at 10 mg/day (Fig. 1B).…”
Section: Gastroesophageal Reflux Diseasementioning
confidence: 99%